Chromosomal localization of ribosomal genes and telomeric sequences in Nephropidae (Crustacea,Decapoda) - COLUCCIA, ELISABETTA; SALVADORI, SUSANNA; DEIDDA, FEDERICA; CAU, ANGELO; DEIANA, ANNA MARIA (country:GRC, 2012)
Introduction Nephropidae family comprises 43 species two of which are present in the Mediterrean sea. Although many species are important commercially and well studied, only 5 species have been analized citogenetically This study aims to deepen the cytogenetic characterization of three species of Nephropidae: Nephrops norvegicus (L), Homarus gammarus (L) and H. americanus H. Milne Edwards, by chromosome localization of the highly conserved major ribosomal gene family and the pentanucleotide (TTAGG) telomeric repeat, the most widespread telomeric sequence among arthropods. Material and methods Mitotic and meiotic metaphases were obtained from gonad tissue of adult males of the three species by the air-drying technique. Fluorescence in situ hybridization (FISH) was performed on chromosomal preparations by using a 45S rDNA and a pentameric (TTAGG) repeat as probes. Results The 45S rDNA FISH localize the major ribosomal genes in the three lobsters in several chromosomal pairs. In the three species, (TTAGG) repeat FISH produced bright fluorescent signals at the end of the chromosomes, furthermore strong signals in interstitial position (ITS) were observed. Discussion The chromosome complement of N. norvegicus, H. gammarus and H. americanus is made up of a high number of little size chromosomes, more than 100 in all species; furthermore in N. norvegicus and H. americanus supernumerary chromosomes have been reported (Coluccia et al., 2004). This is the first report of ribosomal genes localization by FISH in Nephropidae; mulitple NORs have been already observed in other decapods like Palinurus elephas (Coluccia et al., 2006). The presence in the lobsters of the TTAGG repeat as telomeric sequence is in accordance with the hypotesis that the pentanucletide TTAGG is an ancestral motif of telomeres for arthropods and the presence of ITS could be the remnant of chromosome rearrangements and/or inequal crossing-over.